CONCEPTUAL BASIS OF THE FORMING PROFESSIONAL COMPETENCE OF THE FUTURE PROFESSIONALS IN DENTISTRY (Educological discourse, 2014)
The article examines the conceptual foundations of the phenomenon of professional competence of future dentist. Copyright formulated a definition of "professional competence of the dentist", studied its contents, approaches and conditions to ensure effective implementation.